Penerapan Cheerful Literacy Games dalam Meningkatkan Motivasi Belajar Anak-anak yang terdampak Erupsi Sinabung - Syafira Putri Lubis, Lailan; Kusyani, Diah; Novita Harahap, Yenni; Adawiyah Siregar, Rabiatul; Nurhayati; Arianto; Putri, Hartati (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2023)
The natural phenomenon of the continuous eruption of Mount Merapi has made the children of the relocation area of Theosal in the Desa Simacem, Kabupaten Karo, see psychological problems from having to evacuate for a long time, experiencing direct eruption disasters, losing their homes and other possessions, and decreasing motivation to learn due to a learning emergency. This Community Service aims to increase motivation to learn Indonesian in elementary school-age children affected by the eruption of Mount Sinabung in the Siosar Relocation Area, Desa Simacem, Kabupaten Karo. The method used is a workshop event through educational games with cheerful literacy games activities to increase the learning motivation of students of elementary school age in grades 4 to 6 in learning Indonesian. This activity was attended by six lecturers as trainers, one student of the Indonesian Language Education Study Program, and 30 students of State Elementary School No. 047175 Simacem Bekerah, Namanteran District, North Sumatra Province. The material presented in this activity is guessing words, delivering chain messages, and guessing pictures, which they are then asked to explain through telling stories from fairy tales that have been read and competing to answer questions quickly to improve listening skills in elementary school-aged children. The community service program implemented by the Indonesian Language Education Study Program, FKIP Alwashliyah University Medan, has been carried out very well and received a positive impression from all participants. The existence of a cheerful literacy games workshop program has an impact on increasing children's interest and learning motivation, as can be seen from their enthusiasm for participating in each activity and asking questions to understand better the material presented.